Oral health of children with asthma - Tarigan, Nina Stephane Gusratylova; Soewondo, Williyanti; Runkat, Jakobus (Padjadjaran Journal of Dentistry, 2014)
Introduction: Asthma is a chronic disease, most prevalent in children. Oral manifestations can be found in children with asthma such as dental caries and periodontal disease. The purpose of this research was to obtain  the condition of oral health children with asthma. Methods: The research was a descriptive and the survey technique. Subjects were taken using the Randome sampling technique. Subjects who are diagnosed with asthma are gathered from the Children Department, Pulmonary Hospital Dr.H.A Rotinsulu Bandung. The amount of 36 child with asthma will become the receasrch subjects. Data was obtained by clinical examination using def-t index, DMF-T index, the prevalence of caries, oral and dental hygiene status which also obtained by plaque index of PHP and prevalence of dry mouth. Results: def-t index was 3,38, DMF-T index was 0,30, the prevalence of caries was 80,6%. The mean of oral and dental hygiene status of child with asthma was 21 child (58,3%) making it mostly in a poor category and prevalence dry mouth was 91,7%.Conclusion: def-t index is medium, DMF-T index is very low, prevalence of caries is relatively high,and the mean of oral hygiene status has poor category, and also the relative high prevalence of dry mouth.